2001
DOI: 10.1088/0031-9155/46/2/313
|View full text |Cite
|
Sign up to set email alerts
|

Response characterization of ammonium tartrate solid state pellets for ESR dosimetry with radiotherapeutic photon and electron beams

Abstract: Solid state pellets (1 mm thick) for electron spin resonance (ESR) dosimetry were made using ammonium tartrate as the radiation-sensitive substance. Their behaviour was experimentally investigated as a function of dose with 60Co gamma rays. The calibration function obtained permits measurements of absorbed dose in the 2-50 Gy range, with a combined uncertainty of +/-4%. The lowest detectable dose was about 0.5 Gy. These properties are comparable with or even better than those of ESR dosimeters made from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Knowledge of time stability of the EPR signal intensity under different storage conditions after irradiation is of great importance from the dosimetric applications point of view (Arber and Sharpe, 1993;Nagy and Desrosiers, 1996;Bartolotta et al, 2001). Fig.…”
Section: Time Dependencementioning
confidence: 99%
“…Knowledge of time stability of the EPR signal intensity under different storage conditions after irradiation is of great importance from the dosimetric applications point of view (Arber and Sharpe, 1993;Nagy and Desrosiers, 1996;Bartolotta et al, 2001). Fig.…”
Section: Time Dependencementioning
confidence: 99%
“…Although, some researcher reported that AL could be used in the determination of radiation doses below 10 Gy by using some extra techniques (Anton, 2006;Bafa and Kinoshita, 2014;Castro et al, 2006;Sharpe et al, 1996;Sharpe, 2003;Haskell et al, 1998) many researchers exploring to find new materials sensitive to low radiation doses (Alzimami et al, 2014). In this regard, smart phone screen glass, sugar, some tartrate salts, compounds of formic acid and dithionate salts have been evaluated in the literature (Fattibene et al, 2014;Trompier et al, 2011;Yordanov et al, 2002;Mikou et al, 2009;Olsson et al, 2000;Yordanov and Gancheva, 2004;Bartolotta et al, 2001;Tuner and Korkmaz, 2009;Korkmaz et al, 2012;Bal and Tuner, 2014a;Vestad et al, 2003;Gustafsson et al, 2004;Danilczuk et al, 2008;Baran et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ESR technique has become an international standard for dose measurements through alanine (13). However, in the last decade various new materials have undergone detailed analyses and studies designed to improve the effectiveness of ESR in radiation detection, including various organic and inorganic compounds such as ammonium tartrate (14,15), lithium lactate (16), magnesium lactate (17), and formates and dithionates (18). These compounds show good sensitivity for photon and electron beams, but the response for thermal neutrons is very inadequate.…”
Section: Introductionmentioning
confidence: 99%